Optimization of Malaysia rice MR219 derivatives cell suspension culture and responses of stress-related enzymes under drought condition - Er, Choon Yeong (2019)
Rice is the staple food for a majority of the population around the world. Drought is one of the many factors that affect rice production yield. Researches have used various methods to develop suitable indicator in rice to defend the crop against drought environment. Among the biotechnology techniques, cell culture is commonly used to develop drought tolerant cell line. In Malaysia, drought has greatly affected rice production; as water is the essential element for rice and the heavy dependence of rice on irrigation will make rice as the crop most affected by water shortage crisis. Hence, it is a need to develop drought-tolerant rice in order to fulfil rice demand in Malaysia.The aim of this research is to investigate the biochemical responses in Malaysian rice by using plant cell culturing technique under water-limited condition. The cell suspension of Malaysian rice MR219 line 4 was established and it was cultured in vitro with drought agent (PEG6000) in order to prevent water up take by plant cell. After that, biochemical analyses were performed such as glyoxalase I (Gly I) enzyme assay, methylglyoxal, antioxidant enzymes activities – superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), and lipid peroxidation of PEG6000 treated cultures were determined. The results showed that while PEG6000 concentration increased from 0%, 5%, 10%, 15% to 20%, the settle cell volume (SCV), cell viability and relative water content (RWC) were declined maximum to 115%, 34% and 24% respectively as a result of drought condition. When drought stress occurred, it eventually activated the plant cell defensive system by upregulating antioxidant enzymes activities (SOD, CAT and APX) to overcome oxidative injury under drought stress condition. It exhibited the highest relative activities for SOD (13.7708 U / mg proteins), CAT (0.1238 μmoL / mg protein / min) and APX (0.4852 μmoL / mg protein / min). Same trend has been applied to Gly I (4.4633 μmoL / mg protein / min). It implicated that the Gly I could be one of the potential drought stress indicator for rice. The output of this study would contribute tremendously to exploit potential drought-tolerant rice cultivar in the future.